Pemanfaatan tepung kulit pisang kepok (Musa balbisiana colla) dalam formulasi pakan ikan nila (Oreochromis niloticus) - Jeharu, Albertus A.Y; Lumenta, Cyska; Sampekalo, Julius (Universitas Sam Ratulangi, 2015)
The objectives of this research was to determine the effect of feeding with different compositions of meal banana skin to the relative growth, absolute growth, feed efficiency and the best value for tilapia fish. This research was conducted at the Laboratory of Aquaculture Technology Faculty of Fisheries and Marine Sciences of Sam Ratulangi University. The fish samples used in the study was tilapia fish with a length of 3-5 cm with an average weight of 0.8-1 g.Â Feed used as treatments contanined different banana skin powder including treatment A:10%, B 20%,Â C 30%,Â D 40%, and E 50% banana skin powder. Fish was cultured in an aquarium equipped with a recirculation system. The parameters observed included absolute growth, relative growth and feed efficiency value. The experimental design used was complete randomized design (CRD) with five treatments, each with three replications. The results showed that feeding with feed containing 20%banana skin powder gave the highest absolute growth value of 2.93. Feeding with 10% banana skin powder gave the highest relative growth (363%) the highest feed efficiency value is 46.6%. Keywords: banana skin powder (Musa balbisiana colla), absolute growth, relative growth, feed efficiency, Oreochromis niloticus